2018
DOI: 10.1177/1052562918786992
|View full text |Cite
|
Sign up to set email alerts
|

You’ve Been Framed! The Effect of Opportunity and Prosocial Framing on the Novelty and Usefulness of Student Solutions

Abstract: Creativity, the production of ideas that are both novel and useful, is increasingly important to businesses' long-term success. This study looks at whether instructors can use framing-increasing the saliency of some aspects of a perceived reality in a communication-to affect the creativity of student solutions. More specifically, building on research on issues interpretation, the study examines the effect of opportunity framing on the novelty of student ideas. Building on the literature on perspective taking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 130 publications
(225 reference statements)
0
4
0
Order By: Relevance
“…In addition, considering the influence of knowledge diversity on innovation behavior, Sun Y. et al (2020) reported that prosocial interaction helps innovators overcome the problem of knowledge diversity. Besides, Bertels (2018) explored the difference between the influence of prosocial motivation on novelty and the influence of prosocial motivation on the usefulness of creativity. He reported that members who received an assignment description that included opportunity framing produced more novel solutions, whereas those who received the same assignment but with prosocial framing created less useful solutions.…”
Section: Literature Review and Theoretical Basismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, considering the influence of knowledge diversity on innovation behavior, Sun Y. et al (2020) reported that prosocial interaction helps innovators overcome the problem of knowledge diversity. Besides, Bertels (2018) explored the difference between the influence of prosocial motivation on novelty and the influence of prosocial motivation on the usefulness of creativity. He reported that members who received an assignment description that included opportunity framing produced more novel solutions, whereas those who received the same assignment but with prosocial framing created less useful solutions.…”
Section: Literature Review and Theoretical Basismentioning
confidence: 99%
“…How to solve the optimal solution of prosocial motivations that facilitate different types of innovation behaviors needs to be further explored. On the other hand, previous analyses of the internal composition and characteristics of innovation behavior are insufficient ( Bertels, 2018 ). According to the output process of innovation, innovation behaviors can be specifically divided into basic research behavior, applied research behavior, basic-to-applied transformation behavior, and applied-to-basic transformation behavior.…”
Section: Literature Review and Theoretical Basismentioning
confidence: 99%
See 1 more Smart Citation
“…Experiential learning approaches to the teaching of entrepreneurial tools have been developed and presented in the literature—however, these are often in small class settings that allow for hands-on instruction and close student–lecturer engagement (Schmidt et al, 2012; Bertels, 2018; Parris & McInnes-Bowers, 2019; Schumacher & Mayer, 2018) or without discussing the challenge of large (Mason & Arshed, 2013) or postgraduate (Nabi et al, 2017) classes. Proponents of experiential approaches to entrepreneurship education acknowledge the pressure for larger classes and the obstacles this places in the way of providing for experiential teaching (Fulgence, 2015; Henry, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%